Digestibility of diets with passion fruit by-product estimated through external and internal markers in dairy heifers - Figueiredo, Mércia Regina Pereira de; Saliba, Eloisa de Oliveira Simões; Barbosa, Geraldo Sérgio Carneiro; Colodo, Juliana Cristina Nogueira; Almança, Rebeca Agnes; Moreira, Guilherme Rocha (Acta Scientiarum. Animal Sciences, 2020)
This study examined the influence of the external markers chromium oxide (CO), titanium dioxide (TD), isolated, purified and enriched lignin (LIPE®) and isolated, purified, enriched lignin in nanoparticles (NANOLIPE®) as well as the internal markers indigestible dry matter (iDM), indigestible neutral detergent fiber (iNDF) and indigestible acid detergent fiber (iADF) in diets with inclusion of passion fruit by-product for dairy heifers on the estimation of fecal output and nutrient digestibility. Sixteen Holstein × Zebu crossbred heifers at an average live weight of 363 ± 28 kg were randomly distributed in a completely randomized design where they received diets in which Tifton 85 (Cynodon sp.) hay was replaced with passion fruit by-product (0, 12, 24 and 36%, as-fed basis). The CO, LIPE®, NANOLIPE® and iNDF markers did not differ from the total collection method (p > 0.05) in the estimation of fecal output and nutrient digestibility. The TD and iDM markers overestimated, while iADF underestimated fecal output. Under the presented conditions, we recommend using the CO, LIPE®, NANOLIPE® and iNDF markers to estimate fecal output and nutrient digestibility in diets with inclusion of passion fruit by-product for dairy heifers.